HEDONISTâ€™S HIDDEN FEAR IN OSCAR WILDEâ€™S NOVEL â€œTHE PICTURE OF DORIAN GRAYâ€ - Sulistiyani, Reny Dwi (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2012)
This study is about hidden fear which is felt by the hedonist main character represented in the novel â€œThe Picture of Dorian Grayâ€. The objectives are to find out how hidden fear described in the novel, the reasons why the main character hid his fear, and how the hidden fear regarded as hedonistâ€™s fear. This research is descriptive qualitative. The data were taken in the form of phrases, sentences, paragraphs, and dialogues from the novel. They were gathered by reading, identifying, classifying, selecting, analyzing, and reporting. Sigmund Freudâ€™s theory of Id, Ego and Superego was used in this study. The results of this study are 1) life is a choice, when you choose the right choice you will get the rewards, but if you choose the wrong choice, prepare yourself for getting punishment. 2) Although it surely has reasons, breaking the rules and committing crimes for hiding fear are unforgiveable. 3) Surroundings and social intercourse could influence peopleâ€™s character. As for the further researchers, that this study can be used as one of the references and hopefully, the causes and effects of being hedonist is going to be the next title for the future research.